The antioxidant effect of Michauxia campanuloides on rat ovaries - KURT, S; KOCA, RH; HÜRKUL, MM; SEKER, U; KÖROĞLU, A (Journal of the Hellenic Veterinary Medical Society, 2021)
This study investigated how Michauxia campanuloides affects the Proliferating Cell Nuclear Antigen (PCNA) expression in granulosa cells, the ovarian histomorphology and serum total antioxidant capacity (TAC) in rats. Rats were divided into control (C), treatment 1 (T 1) and treatment 2 (T 2) groups. The rats in the T 1 and T 2 groups received aqueous extract of M. campanuloides at doses of 20 mg/kg/day and 40 mg/kg/day orally for 21 days, respectively. Serum TAC levels, follicles counts including primordial, primary, preantral, antral and atretic follicles, and PCNA expression in granulosa cells were evaluated. Numbers of preantral follicles increased in T 1 and T 2 groups compared to C group (P < 0.05). TAC and numbers of preantral and antral follicles increased in T 2 group compared to T 1 and C groups (P < 0.05). PCNA expression in granulosa cells was increased in T 2 group compared to T 1 and C groups (P < 0.01). In conclusion, treatment with M. campanuloides had positive effects on antioxidant activity, follicular dynamics, and PCNA expression of granulosa cell in rats.